(untitled) (The Pakistan Development Review, 2004)
South Asia is home to nearly 1.4 billion people, a vast part of humanity. The countries in the region vary widely in the size of the population as well as area and physiography. On one side of the scale is India with a population of more than a billion while on the other side is Maldives with a population no more than half a million. There is Bangladesh which is essentially a flat delta, island countries such as Sri Lanka and Maldives and countries full of high rise mountains such as Nepal and Bhutan. In between are India and Pakistan with some of everything. While there are several such external differences among the countries in the region and their people, these are literally only skin-deep. The people in the region share, by and large, the same basic culture. In many cases the same or a similar language is spoken across the borders. There are, of course, local variations in the general pattern. But that diversity makes it all the more interesting and attractive. It is only natural that the countries of the region will band together to show a united face to the world. This is yet to happen, though.